Computerization of Islamic Inheritance Law for Three Categories of Heirs: A Study of Acehnese Manuscript Tables - Arif, Salmawaty; Yuni, Syarifah Meurah; Kadriah; Ratni, Julia (Universitas Islam Negeri Ar-Raniry, 2026)
The paper presents the computerization process of an Acehnese inheritance manuscript. The script summarizes the law in the form of a compact table, written in Jawi script and Arabic. This research extended the table’s formation and content from which only the shares for one and two heir types were provided, to become three heir types. Different from other inheritance researches in quantitative approach, this research introduces the combinatorial methods to obtain all combinations of heirs. Each heir type located in a cell of the table will get the share determined by an algorithm developed to give the priority portion it deserves. The research so far has identified the computerized for three types of heirs out of the total 30 types included as the domain in the manuscript. About 30 percent of the resulting table consisting of 12.180 cells have been verified manually. Further purpose is to re-implement the usage of the table in Muslim daily use as well as broader advantages in preserving the knowledge and local wisdom.